Organizational Justice and Employees Service Behavior in the Healthcare Organizations in Bangladesh: An Agenda for Research (Bangladesh Journal of Bioethics, 2015)
Bangladesh is aspiring to achieve universal health coverage by 2030. In this regard, quality and efficient healthcare delivery have been regarded as a major challenge. Proper management of employees is crucial for service organizations like healthcare because in healthcare employees provide life saving services which make them unique from other non-health professionals. They directly interface with the patients or service seekers who make evaluative judgment of the quality of service delivered by the employees. Therefore, it is important that healthcare organizations (both public and private) comprehend specific organizational factors and issues that influence employees attitudes and behaviors, which ultimately affect their service behaviour at work. Drawing from the organizational justice principles and other management theories, this article presents a conceptual framework and a set of hypotheses regarding the relationships among distributive justice, procedural justice, interactional justice, employees citizenship behaviour, role prescribed behaviour and counterproductive behaviour for the healthcare organizations in Bangladesh. The purpose is to assist the policy makers and service providers in identifying desirable human resource management practices that healthcare organizations in Bangladesh should seek and engage in and at the same time, avoid undesirable practices in order to maintain optimum level of employee commitment, and citizenship behavior essential for ensuring quality and efficient service delivery to the communities. This article is theoretical but it has practical implications for the policy makers and service providers who are directly involved with service delivery system. It is also expected that the paper enriches the health service delivery literature and also advocates focusing on justice perspectives particularly in Bangladesh.